A review of optimization algorithms in solving hydro generation scheduling problems - Hammid A.T.; Awad O.I.; Sulaiman M.H.; Gunasekaran S.S.; Mostafa S.A.; Kumar N.M.; Khalaf B.A.; Al-Jawhar Y.A.; Abdulhasan R.A. (MDPI AG, 2023)
Electric power systems; Heuristic methods; Hydroelectric power; Optimal systems; Scheduling; Generation scheduling of hydro-systems; Meta-heuristic optimizations; Optimal generation; Optimization algorithms; Optimization approach; Optimization procedures; Optimization techniques; Short-term hydro scheduling; Optimization